Inflammatory Disorders of the Nervous System : Pathogenesis, Immunology, and Clinical Management - Minagar, Alireza; Alexander, J. Steven (Springer International Publishing : Imprint: Humana Press, 2017)
This thoroughly updated edition covers all clinical aspects of neuroinflammation. The latest developments in pathogenesis and advances in treatment are provided, along with an understanding of the immune system's role and interactions between the activated immune cells, cerebral endothelial cells, and other main components of the immune cascade. Cutting-edge and authoritative, this volume offers practitioners a valuable resource for research and clinical practice.
Keywords: Medicine.; Neurology.; elektronické knihy; electronic books